New Refinements and Improvements of Some Trigonometric Inequalities Based on Padé Approximant - Lina Zhang; Xuesi Ma (Journal of Mathematics)
A multiple-point Padé approximant method is presented for approximating and bounding some trigonometric functions in this paper. We give new refinements and improvements of some trigonometric inequalities including Jordan’s inequality, Kober’s inequality, and Becker-Stark’s inequality. The analysis results show that our conclusions are better than the previous conclusions.